Two versus three doses of COVID-19 vaccine and post-vaccination COVID-19 infection in hemodialysis patients - Laila A. Ahmed; Hayam H. Mansour; Salwa I. Elshennawy; Marwa A.A. Ramadan; Mohamed A.M. Kamal; Soso S. Mohamed; Omaima Mohamed Ali; Amal H. Ibrhim (Elsevier, 2024)
Summary: Background and aim: Patients with chronic kidney disease including those undergoing hemodialysis (HD) constitute a particularly challenging group regarding COVID-19 vaccination. The present study aimed to compare the rate of reinfection after two and three doses of Sinopharm COVID-19 vaccine in HD patients. Patients and methods: The study included 80 HD patients who received three doses of Sinopharm COVID-19 vaccine. In addition, there were another 80 patients who received only two doses of the vaccine. Patients in the latter group were selected based on propensity matching score with 1:1 ratio. Patients were monitored for post-vaccination COVID-19 infection using PCR examination of nasopharyngeal swabs. Patients were also monitored for post-vaccination complications including general complaints (headache, fever, fatigue), injection site complaints (arm pain, swelling, itching, rash), musculoskeletal complaints (muscle spasm or pain, joint pain) and others. All patients were followed for six months. Results: The present study included 80 patients submitted to COVID-19 vaccination with two doses of Sinopharm vaccine (GI) and other 80 patients who received three doses of the same vaccine (GII). At the end of follow up, 11 patients (13.8 %) in GI caught COVID-19 infection. In contrast, no patient in GII had infection (P<0.001). Comparison between patients who had COVID-19 infection and those without infection revealed that the former subgroup had significantly lower BMI (23.3 ± 2.3 versus 27.5 ± 8.1 Kg/m2), higher frequency of associated Hepatitis C (HCV) infection (54.6 % versus 2.9 %, P<0.001) and higher serum ferritin levels [median (IQR): 1101.0 (836.0-1564.0) versus 675.0 (467.0-767.7) ng/mL, P=0.01]. Binary logistic regression analysis identified high serum ferritin levels [OR (95% CI): 0.014 (0.001-0.15), P<0.001] and associated HCV infection [OR (95% CI): 0.99 (0.98-1.01), P=0.02] as significant predictors of post-vaccination COVID-19 infection in multivariate analysis. Conclusions: A three dose regime of Sinopharm COVID-19 vaccine associated with significantly lower rate of reinfection COVID-19 infection in HD patients. Infected patients had significantly lower BMI, higher frequency of HCV and higher ferritin levels.